Contrasting English Pedagogies in Indonesian and Thai Private Schools:: A Comparative Literature Review - Doloh, Firdow; Hadiyanto, Hadiyanto (Universitas Jambi, Magister Program of English Education Department, 2025)
English has become a crucial language in Southeast Asia, particularly in the context of ASEAN integration, where communication, education, and regional cooperation heavily rely on English proficiency. This study aims to compare English teaching approaches in private upper secondary schools in Indonesia and Thailand, an area of comparison that remains underexplored. The research employs a systematic literature review guided by the PRISMA protocol, selecting 20 peer-reviewed articles published between 2018 and 2024 from Scopus, Google Scholar, and ThaiJo databases. A qualitative thematic analysis and basic quantitative mapping were used to identify trends and divergences across the two countries. The findings reveal similarities in the widespread adoption of Communicative Language Teaching (CLT) and Task-Based Language Teaching (TBLT), with a mutual emphasis on learner-centered and communication-oriented pedagogies. However, the review also reveals significant differences in the integration of the Common European Framework of Reference (CEFR), teacher training systems, and the extent of national policy implementation. Deeper challenges include a mismatch between curriculum policies and classroom realities, a lack of teaching resources, and uneven teacher readiness. The novelty of this article lies in its comparative ASEAN-focused lens and its integration of CEFR-based instructional analysis. The implications are substantial for curriculum designers, policymakers, and educators, particularly in enhancing regional collaboration, promoting continuous professional development, and integrating technology to improve the quality of English language teaching across Southeast Asia.